The Role of Professional Certification Bodies in Enhancing Islamic Higher Education Quality - Yudiawan, Agus; Darwis, Anwar (Institut Agama Islam Negeri Sorong, 2025)
Improving the quality of Islamic higher education in Indonesia requires a quality assurance system that focuses not only on academic aspects but also on graduates’ professional competence. The Professional Certification Institutions or Lembaga Sertifikasi Profesi (LSP) serves as a strategic instrument for bridging the gap between the world of education and the world of work. This article analyzes the role of LSP in improving the quality of Islamic higher education, focusing on policy, implementation, and its contribution to strengthening graduates’ competitiveness. This research uses the library research method, examining academic literature, regulations, and relevant institutional reports. The results of the study show that the presence of LSP in Islamic universities significantly improves the quality of graduates, especially by strengthening employability, curriculum relevance, and a culture of institutional quality. LSP also serves as a means of integrating professional competence with Islamic values, making certification not just a technical assessment but also a process of shaping Islamic character and work ethics. However, the effectiveness of LSP implementation remains influenced by human resource challenges, limited testing facilities, and a lack of synergy between academic curricula and industry standards. This study concludes that strengthening LSP in Islamic universities should focus on developing assessor capacity, digitizing the certification system, and fostering sustainable collaboration with the industrial world and Islamic institutions. With professional governance and Islamic values, LSP can be the main catalyst in realizing superior, relevant, and globally competitive Islamic higher education.